Quantitative Analysis of the Impact of Digital Transformation on Museum Management: Examining Visitor Satisfaction and Engagement Through Augmented Reality (AR) and Virtual Exhibitions in the UK Art Museums - Xing, Hong; Sun, Zhanfang (Journal of Ecohumanism, 2025)
Introduction: Digital technologies such as AR and Virtual exhibitions are changing the art and cultural industry such as museums by impacting visitor engagement and satisfaction. In the UK, the museum sector represents a broad landscape due to the vast number of museums, in which these technologies are implemented to address the challenges of declining visitors and enhancing visitor satisfaction. Objective: This study purported to investigate the impact of AR and Virtual Exhibitions on visitor engagement and satisfaction in UK art museums. Methodology: A cross-sectional research design was employed, collecting data from 155 respondents through a structured questionnaire based on the Technology Acceptance Model (TAM). Results: The results revealed that AR and Virtual exhibitions have a positive impact on visitor engagement and satisfaction though moderated by factors such as technical usability, visitor demographics and museum types. Here, larger museums have more resources which demonstrates greater capacity to adopt digital transformation, while smaller museums may have to face resource constraints. Conclusion: In a nutshell, it can be said that AR and Virtual Exhibitions can enhance museum experiences and foster long-term visitor behaviours such as repeat visits and positive word of mouth. Hence, the hybrid model of museums us critical for museums to combine all the digital and physical experiences for diverse audiences.